Content Based Image Retrieval: An overview of structure of the image and image database - Barathy, G.; Mahesan, S.; Pinidiyaarachchi, U.A.J. (SLIIT, 2011)
There are a number of challenging problems in Content Based Image Retrieval (CBIR) particularly on structure of the image and image database. Separating an image into its constituent parts is a major task in this area. In fact, an image indexing system will have to be developed. It should extract the main perceptual components in the image, their properties and relationships among them. Furthermore, storing images in a large database and retrieving them from the database in an efficient way is another major task in this area. This paper reviews the techniques used for image structure analysis and structure of the image database for CBIR to overcome the problems arising in these areas.
Keywords: Content based Image Retrieval, feature extraction, image databases